2017
DOI: 10.1371/journal.pone.0186677
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of dog owner-charged rabies vaccination in Kinshasa, Democratic Republic of Congo

Abstract: Rabies is a preventable fatal disease that causes about 61,000 human deaths annually around the world, mostly in developing countries. In Africa, several studies have shown that vaccination of pets is effective in controlling the disease. An annual vaccination coverage of 70% is recommended by the World Health Organization as a control threshold. The effective control of rabies requires vaccination coverage of owned dogs. Identification of the factors determining dog owners’ choice to vaccinate is necessary fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
(16 reference statements)
3
9
0
Order By: Relevance
“…Moreover, we found that dog owners who ever heard of rabies were 12.3 times more likely to vaccinate their dogs against the disease than those who did not. This is not surprising as education has been noted as an important predictor of health decision making [46]. This finding is consistent with studies done in Tanzania and Pakistan where respondents with secondary and tertiary education were associated with having better knowledge of rabies [47,48].…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, we found that dog owners who ever heard of rabies were 12.3 times more likely to vaccinate their dogs against the disease than those who did not. This is not surprising as education has been noted as an important predictor of health decision making [46]. This finding is consistent with studies done in Tanzania and Pakistan where respondents with secondary and tertiary education were associated with having better knowledge of rabies [47,48].…”
Section: Discussionsupporting
confidence: 88%
“…Despite recurrent rabies outbreaks across the DRC, the disease remains neglected with few rabies-focused studies limited to Kinshasa [26,28,29,31]. Controlling rabies in the animal reservoir through mass dog vaccination is the most cost-effective and sustainable approach to prevent dog-mediated human rabies cases [2,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, 21 clinically-confirmed rabies cases in children were registered in the Pediatrics Department of a single hospital in the capital city of Kinshasa in only seven months. In a retrospective study of 5053 animal attacks in Kinshasa between 2009 and 2013, 2.5% were likely due to rabid animals [28]. Despite this alarming situation, no official rabies control program is in place and very limited data on dog population and community awareness regarding rabies exist.…”
Section: Introductionmentioning
confidence: 99%
“…In the endemic areas of rabies, a minimum of 70% of the dog population in each year during 5-7 years should receive the vaccination [48]. The crucial vaccination coverage ranges from 25-40% [41]. It is essential to interrupt rabies transmission.…”
Section: Mass Parental Vaccination In Dogsmentioning
confidence: 99%